PERAN PENYULUH PERTANIAN LAPANGAN (PPL) DALAM MENDUKUNG ADOPSI BUDIDAYA TANAMAN KOPI ARABIKA YANG BAIK (GOOD AGRICULTURE PRACTICES) OLEH PETANI DI KABUPATEN TAPANULI SELATAN - Yuliana Kansrini; Puji Wahyu Mulyani; Dwi Febrimeli (Politeknik Pembangunan Pertanian Medan, 2020)
This study examines the role of Agricultural Extension Workers (PPL) in supporting the adoption of good agricultural practices by farmers in South Tapanuli Regency. The basic objective in this study was determine the level of the role of PPL in supporting the adoption of good agricultural practices by farmers in South Tapanuli Regency. The basic for selecting the location of the study was purposive method. This type of research is quantitative with analytical descriptive method. The sample was determined by purposive method in accordance with the criteria in this study as many as 40 people. Data collection techniques carried out by in-depth interview and filling out the questionnaire. Data analysis was performed by tabulating quantitative data from the assessment result with a Likert scale. The results showed that PPL’s role in supporting the adoption of good agricultural practices for Arabic coffee by farmers in South Tapanuli Regency was in the moderate category at 66.24 percent. The level of PPL role as facilitator gets the highest percentage of 70.00 percent compared to the level of other roles. Meanwhile, PPL’s role as monitoring and evaluation obtained the lowest percentage of 57.96 percent.